Tilaushistoria identiteettityönä ja kulttuuriperintöprosessina – Paikallisen historiapolitiikan tarkastelua - Sivula Anna (Kulttuuripolitiikan tutkimuksen seura, 2022)
This article is concerned with commissioned histories and the use of histories. Cultural
heritage is created and recreated in a process of the identity work, where a heritage
community uses different histories to add the cultural value of the remnants of the past.
A heritage community is a participating group of actors, involved in a certain process of
identity work, and voluntarily taking part in the cultural heritage production. The members
of heritage communities use different kinds of histories for to consolidate their sense of
ownership of the remnants of their own past and for to strengthen their sense of belonging
and togetherness. A heritage community can be either local or translocal. In this article I
introduce three different types of identity work and clarify how they interact in the process
of cultural heritage. I also give some new methodological tools for the researchers, who
want to understand the emergence of temporary heritage communities and who are interested
in the cultural heritage production “from below”.